Challenges to Accounting Education in Higher Economic Education - Nedelin Markov; Nadka Kostadinova (Икономика и компютърни науки, 2025)
Accounting can be referred to as the "language" of business. For the needs of management, it provides comprehensive and exhaustive information within the enterprise about the tangible, labor, financial and natural resources, and their utilization. The purpose of this publication is to analyze the challenges accounting education faces at university level. We, therefore, applied the methods of induction and deduction, survey research and statistical methods. The results show that further adaptation is needed to align the taught accounting courses with the subjective perceptions of students.